THE CONCEPT OF LEGAL REGULATION OF ELECTRONIC COMMERCE - Zhumadilova M.A.; Dussipov Ye.Sh.; Aitimov B. Zh. (Academic Journal of Physical and Chemical Sciences, 2020)
The social relations taking place in electronic commerce and the category “electronic commerce” are studied, the qualifying features of this activity are identified, the correlation of the concepts “trade” and “electronic commerce” is made and the author’s definition of the concept and subject of legal regulation of public relations in the field of electronic commerce is developed. Thus, electronic commerce is often considered as a special form of transactions, in which their conclusion and execution is carried out using electronic means of communication. At the same time, the legal characteristics of transactions remain unchanged, and they must be regulated by the rules of law that regulate relations of the appropriate type (purchase-sale, transportation, contract, rent, etc.). According to this position, electronic data exchange does not change the essence of the relationship between the parties and affects only the form in which these relations are built. Within this approach, several points of view have been formed. A number of specialists consider electronic commerce as the production, advertising, sale and distribution of goods using telecommunication networks. Others interpret it as electronic business. In the world practice, the term “trade” has also been widely interpreted so that it covers issues arising from all relations of a commercial nature, both contractual and non-contractual. Trading relationship includes the transactions as follows: any trade transactions for the supply of goods or services or the exchange of goods or services; distribution agreements; commercial representation and agent relations, factoring; leasing; construction of industrial facilities; consulting services; engineering; purchase and sale of licenses; investment; financing; banking services; insurance; operating or concession agreements; joint ventures and other forms of industrial or business cooperation; transportation of goods and passengers by air, sea, train or car. One should recognize that such a broad understanding of trade does not contribute to a detailed study of this concept and it is not suitable in practice. Therefore, the economic meaning of the term "trade" is widely spread in modern science. In a broad sense, trade is considered as a branch of the national economy that ensures the circulation of goods, their movement from the sphere of production to the sphere of circulation. In a narrower sense, trade is defined as economic intermediation between producers and consumers which is carried out by the purchase of goods from producers in order to sell them to consumers and their further sale to other consumers. Electronic commerce is proposed to understand the implementation of actions provided for by law, other operations in the execution of transactions for the sale of goods, work and services based on electronic procedures by the parties of the transaction. At the same time, it is proposed to understand electronic procedures as a special procedure (rules, regulations) for electronic operations in a transaction, and electronic operation on a transaction as performing certain actions by the parties to the transaction to execute the transaction through remote interaction of the parties of the transaction, other entities and their information systems in electronic commerce.